2007
DOI: 10.1007/s00330-007-0684-0
|View full text |Cite
|
Sign up to set email alerts
|

The intravertebral vacuum phenomen as specific sign of osteonecrosis in vertebral compression fractures: results from a radiological and histological study

Abstract: This study investigated the prevalence of the intravertebral vacuum phenomenon (IVP) and osteonecroses in vertebral compression fractures (VCFs). We therefore performed an histological analysis of biopsies obtained from VCFs prior to balloon kyphoplasty. Computed tomography (CT) scans were reviewed regarding the presence of an IVP (i.e. cleft sign, Kümmell disease). We reviewed the data of 266 consecutive patients treated by balloon kyphoplasty in 501 procedures from 2002 to 2004. From 180 patients (68%) we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
95
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 29 publications
(39 reference statements)
0
95
0
1
Order By: Relevance
“…The most important risk factors for the development of an intravertebral gas cleft are osteoporotic vertebral fractures, steroid medication, trauma, and radiation therapy (11). Thus a vertebral compression fracture seems to represent the initial event (11).…”
Section: Discussionmentioning
confidence: 99%
“…The most important risk factors for the development of an intravertebral gas cleft are osteoporotic vertebral fractures, steroid medication, trauma, and radiation therapy (11). Thus a vertebral compression fracture seems to represent the initial event (11).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that IVC (10 recompressions out of 24 IVCs) was one of the factors most strongly related to recompression. IVC provides radiological evidence of osteonecrosis [5,19,22,24,27], or nonunion and pseudoarthrosis after vertebral fracture [1,2,11,13,23]. Whatever the reasons, IVC might be made in chronic period of fracture healing process after initial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to obtain the diagnosis of vertebral ON prior to making a decision on treatment, since it should be taken into consideration. Currently, vertebral ON remains a radiographic diagnosis, but most studies correlated the histopathology and image finding from percutaneous needle biopsy [4,25,26]. To the best of our knowledge, only Baur et al [27] reported the histological comparison of fluid sign in four osteoporotic and one metastatic fracture by open retrieval of specimen from surgery.…”
Section: Discussionmentioning
confidence: 99%